A Critical Investigation On Modern Artificial Skull Development Using Advanced Novel Biomaterials In Emerging Medical Industry - Subashree Priyadarsini R, Harini S, Dipti B, Balaji Ramachandran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In the recent years, biomaterials used for reconstructing skull have undergone various development and researches in search of the best biomaterial which could be used. The surgical intervention used to reconstruct cranial bone defects is called cranioplasty, usually caused by injuries due to heavy falls and road accidents. In the modern field of cranioplasty considering the clinical procedures and expenses, the research for getting better reliable and comfortable biomaterials have never stopped. Cranioplasty is also employed in performing cosmetic surgeries. In the succeeding pages, the management of head injury and the process of cranioplasty as well as its complications are listed briefly. In the history of cranioplasty many different types of materials have been used and it is also being continuously evolved for betterment. An ideal biomaterial used for cranioplasty should have properties of lightweight, durability, fixable to the skull, osteoconductivity, and malleability. The principle material and the techniques are reviewed for the critical investigation on modern artificial skull development using advanced novel biomaterials in emerging medical industry. The materials being used for skull replacement are generally based on polymers, metals, ceramics, Nano materials and alloys. Each biomaterial has unique manufacturing techniques and method. The stem cell technique and autologous bones are also used in the process of bone replacement. The composition and properties of each material is explained and a comparative study of materials and techniques based on its performance and recovery of patients is done with the help of previous studies.